Youth, Pornography, and Addiction: A Critical Review - Healy-Cullen S; Taylor K; Morison T (Springer Nature Switzerland AG, 2024)
Purpose of Review: In this article, we dig more deeply into the assumptions underpinning common-sense understandings about youth “exposure” to pornography and the ostensible “effects” of this exposure, specifically “pornography addiction”. We trace the emergence of the notion of “pornography addiction”, highlighting how cultural conditions have allowed for its realisation as a socially recognisable and intelligible narrative. Recent Findings: Media effects research on the issue of youth “exposure” to pornography is not conclusive, nor is pornography addiction officially recognised as a diagnosable disorder. Moreover, an emerging body of multidisciplinary qualitative research, which, importantly, includes the perspectives and experiences of young people themselves, raises questions about some of the assumptions and conclusions of effects-focused research. Summary: Despite inconclusive and contrasting findings, the social narrative of pornography addiction persists both within and beyond academe. We make sense of this persistence in relation to the broader problematisation of youth sexuality, which includes unease and moral objection to young people viewing pornography. It is important to recognise the broader socio-cultural systems supporting the cultural narrative of pornography addiction, and the social functions that this narrative serves, that is, the need for adult intervention into the sexual lives of youth.
Keywords: Pornography addiction; Online pornography; Young people; Adolescence; Media efects